Additional three new species of Anarsia Meyrick (Lepidoptera, Gelechiidae) from Cambodia and Vietnam - Park, Kyu-Tek; Bae, Yang-Seop (Zootaxa, 2017)
Three new species of the genus Anarsia Zeller (Lepidoptera, Gelechiidae) are described: A. huensis Park, sp. nov. from Vietnam, and A. pursatica Park, sp. nov. and A. degeneralis Park, sp. nov. from Cambodia. Images of adults and genitalia for the new species are illustrated. A check list of the known species from both countries is provided.